STRATEGI METODE DAKWAH DALAM MEMAKMURKAN MASJID JAMIE AL- HIKMAH MELALUI PENGAJIAN RUTIN DI DESA WANAJAYA - Tri Mega Utami; Achmad Junaedi Sitika (Jurnal Dakwah Tabligh, 2023)
The research was conducted to find out the strategy of the da'wah method in prospering the Jamie al-hikmah mosque through routine recitations in Wanajaya Village, Kec. Telukjambe Barat, Karawang Regency. This study used a qualitative approach by collecting data using interviews, observation, and analysis of documentation data. The research sources were DKM, mosque administrators, and one of the speakers. The results of this study contain routine recitations including routine religious recitations every Tuesday night and routine yasin and recitations every Friday night. The material comes from classic books including the book of tijan addaruri by Syekh Nawawi al-Bantani, Jauhar at Tauhid by Syekh Ibrahim al-Bajuri, safinatun najah by Syekh Nawawi al-Bantani, fathul muin by Syekh Zainuddin bin Abdul Aziz al- Malibari, bidayatul hidayah by Imam al-Ghazali, al-hikam by Syekh Ibn Atha'illah as well as references to sources from books and notes. The da'wah method strategy used is the lecture method, discussion method, and question and answer method